Ammonia Oxidation in the Ocean Can Be Inhibited by Nanomolar Concentrations of Hydrogen Peroxide - Tolar, Bradley B.; Powers, Leanne C.; Miller, William L.; Wallsgrove, Natalie J.; Popp, Brian N.; Hollibaugh, James T. (Frontiers in Marine Science, 2016)
Marine Thaumarchaeota were discovered over 20 years ago and although a few isolates from this group are now available for study, we do not yet understand the environmental controls on their growth and distribution. Thaumarchaeotes oxidize ammonia to nitrite, mediating a key step in the global nitrogen cycle, and it is estimated that about 20% of all prokaryotic cells in the ocean belong to this phylum. Despite their almost ubiquitous distribution, marine Thaumarchaeota are rarely abundant in open-ocean surface (<100 m) waters. We tested the hypothesis that this vertical distribution is driven by reactive oxygen species (ROS), specifically H2O2, generated by photochemical and biological processes – ‘indirect photoinhibition’ rather than light inhibition as previously postulated for ammonia-oxidizing Archaea. Here we show that H2O2 can be surprisingly toxic to Thaumarchaeota from the Southern Ocean, with ammonia oxidation inhibited by additions of as little as 10 nM H2O2, while temperate Thaumarchaeota ecotypes were more tolerant. This sensitivity could explain the seasonal disappearance of Thaumarchaeota from polar surface waters and the increase in ammonia oxidation rates with depth commonly observed in marine environments. Our results highlight the need for further physiological studies of Thaumarchaeota, and indicate that ROS sensitivity could be used as a characteristic for dividing the group into meaningful ecotypes.